The Influence of Internal Performance and Macroeconomic Conditions on Regional Development Bank Credit Risk in Indonesia Period 2017-2021 - Tri Wahyu Winarso; Surya Raharja (Jurnal Syntax Admiration, 2023)
This study aims to identify the effect of internal performance and macroeconomic conditions on the credit risk of Regional Development Banks in Indonesia in the 2017-2021 period. This research is a quantitative research using statistical data. The population used in this research is Regional Development Banks in Indonesia from 2017 to 2021. The sample used in this research is from 24 Regional Development Banks in Indonesia that have been registered with the Financial Services Authority (OJK). The data for this research were obtained from library sources available at the Financial Services Authority, the Central Bureau of Statistics and Bank Indonesia. The research data was processed using the Error Correction Model (ERM) with Microsoft Excel and Eviews 10 software. The results of this study indicate that the Credit Growth Ratio has a positive effect on NPLs both in the long term and in the short term. CKPN receipts have a positive effect on NPL both in the long term and in the short term, BOPO has a negative effect on NPL both in the long term and in the short term, inflation has a positive effect on NPL both in the long term and in the short term, GRDP has a negative effect on NPL both in the long term and short term.